Learning and change in a dual lexicon model of speech production - Davis, Maya; Redford, Melissa A. (Frontiers in Human Neuroscience, 2023)
Speech motor processes and phonological forms influence one another because speech and language are ac- quired and used together. This hypothesis underpins the Computational Core (CC) model, which provides a framework for understanding the limitations of perceptually-driven changes to production. The model assumes a lexicon of motor and perceptual wordforms linked to concepts and whole-word production based on these forms. Motor wordforms are built up with speech practice. Perceptual wordforms encode ambient language patterns in detail. Speech production is the integration of the two forms. Integration results in an output trajectory through perceptual-motor space that guides articulation. Assuming successful communica- tion of the intended concept, the output trajectory is incorporated into the existing motor wordform for that concept. Novel word production exploits existing motor wordforms to define a perceptually-acceptable path through motor space that is further modified by the perceptual wordform during integration. Simulation results show that, by preserving a distinction between motor and perceptual wordforms in the lexicon, the CC model can account for practice-based changes in the production of known words and for the effect of expressive vocabulary size on production accuracy of novel words.